2016
DOI: 10.1007/s00520-016-3465-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of granulocyte-colony stimulating factor (G-CSF) induced bone pain using double histamine blockade

Abstract: The use of a double histamine blockade is an inexpensive, safe, and effective way to alleviate bone pain symptoms secondary to G-CSF agents. Further investigation is warranted for prospective larger studies to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…sensory neurons that detect noxious stimuli in bone). Agents that have been reported to sensitize bone nociceptors include bradykinin, endothelins, epidermal growth factor, glial cell line‐derived neurotrophic factor, histamine, nerve growth factor (NGF), prostaglandins, tumour necrosis factor and vascular endothelial growth factor . Probably the best studied factor that has been examined in bone pain in both preclinical and human clinical studies is NGF.…”
Section: Sensitization Of Nociceptors Innervating Bonementioning
confidence: 99%
“…sensory neurons that detect noxious stimuli in bone). Agents that have been reported to sensitize bone nociceptors include bradykinin, endothelins, epidermal growth factor, glial cell line‐derived neurotrophic factor, histamine, nerve growth factor (NGF), prostaglandins, tumour necrosis factor and vascular endothelial growth factor . Probably the best studied factor that has been examined in bone pain in both preclinical and human clinical studies is NGF.…”
Section: Sensitization Of Nociceptors Innervating Bonementioning
confidence: 99%
“…HF51116 interrupts the SDF-1α/CXCR4 axis to mobilize more HSCs than is achieved using G-CSF alone. G-CSF shows inter-individual variability and causes bone pain due to its toxic side effects on the BM microenvironment (38,39), and it also require a 4-day standard treatment, which might be too long a treatment duration. The stronger HSC-mobilization activity of HF51116 provides the possibility of reducing the combinatory dose of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of bone pain secondary to G-CSF are not fully known but recent studies have been reported to range from 19 % to 59 %. Bone pain develops in patients treated with pegfi lgrastim and fi lgrastim (2,7,8,11,20,21). On account of bone pain is a well-known complication of G-CSF, pain is treated with drugs (8,9,11,20,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used G-CSF preparations in Turkey and worldwide are fi lgrastim and lenograstim (6). Patients may experience adverse effects including headache, bone pain, myalgia and arthralgia related to G-CSF which are usually managed using pharmacological agents (3,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%